Assessing Risk among Frail Older Adults in Ontario, Canada, during the COVID-19 Pandemic: A Mixed Methods Evaluation of a Telephone Outreach Program. (31st March 2023) - Lee, Linda; Hillier, Loretta M.; Carducci, Jillian; Patel, Tejal; Skimson, Kara; Dillon-Martin, Sharon; Kuzych, Lissa; Beuermann, Lindsay; Parikh, Ruchi; Lee, Catherine
Abstract : We developed a pandemic telephone outreach protocol to identify risk for social isolation, health destabilization, medication issues, inadequate services and supports, and caregiver stress among older adults at high risk of destabilization. Screening, conducted between April 1, 2020, and May 8, 2020, was targeted to those who had previously been screened as frail or who were identified as vulnerable by their family physician. This study describes the implementation and results of this risk screening protocol and describes patient, caregiver, and health professional perceptions of this outreach initiative. Mixed methods included satisfaction surveys and interviews completed by patients/caregivers ( N = 300 and N = 26, respectively) and health professionals ( N = 18 and N = 9, respectively). A medical record audit collected information on patient characteristics and screening outcomes. A total of 335 patients were screened in the early weeks of the pandemic, of whom 23% were identified with at least one risk factor, most commonly related to the potential for health destabilization and medication risk. Follow-up referrals were made most frequently to physicians, a pharmacist, and a social worker. The outreach calls were very well received by patients and caregivers who described feeling cared for and valued at a time when they were socially isolated and lonely. The outreach calls provided access to trusted COVID-19 information and reassurance that health care was still available. The majority of health professionals (>86%) were "very" or "extremely" satisfied with the ease of completing the screening via telephone and value for time spent; for 79% the protocol was "very" or "extremely" feasible to implement. Health professional interviews revealed that patients were unaware they could access care during the pandemic lockdown but were reassured that care was available, potential crises were averted, and they supported future implementation. Risk screening provides a significant opportunity to provide information, support, and mitigate potential risks and is an important and feasible component of pandemic planning in primary care.